The Effectiveness Of Think-Pair-Share In Improving Engineering Department Students Speaking Skill - Sari, Dyan (LPPM Universitas Mercu Buana Yogyakarta, 2016)
This research was conducted based on the students’ ability that was low in speaking which gave negative impact toward students’ final score. This problem was caused by some factors; one of them was the technique of teaching that only focused on the teacher. As a result, the students were not active in teaching learning process. Research method that was used in this research was a quasi-experiment with pre-test post-test control group design. Technique of teaching applied was Think Pair Share. The population of this research was the eleventh grade English department students of SMK Pelayaran Putra Samudera Yogyakarta in academic year 2015/2016 with the total number of students was 50. The sample of this research was XIA with 25 students as experimental class and XIB with 25 students as control class, that were chosen by using purposive sampling. Instrument used in collecting the data was speaking test. The result of the test was analyzed by using t-test. From that test, it was found that tcalculated was higher than t-table, where t-calculated was 3.624 and t-table was 2.011. Thus, Ho was rejected and Ha was accepted. As conclusion there was significant improvement of Think Pair Share Technique applied toward students’ speaking skill at the eleventh grade English department students in academic year 2015/2016.